Multiple short-lived marine incursions into the interior of Southwest Gondwana during the Aptian - Fauth, Gerson (2024)
The Lower Cretaceous sediments of the Sanfranciscana Basin, southeast Brazil, are considered to have been deposited under a Gondwanan continental context. However, different authors have occasionally observed marine elements in these same deposits. This study analyzes samples from five sections of the Sanfranciscana Basin, Quiricó and Três Barras formations, to characterize the paleoenvironment around these marine incursions. We recovered continental (non-marine ostracods and palynomorphs) and marine microfossils (e.g., foraminifera, radiolarians, and ascidian spicules). The alternance of quartz-rich biogenic chert and claystone might be indicative of the occurrence of radiolarites in the studied sessions. The presence of the radiolarian genus Turbocapsula sp., the radiolarian species Holocryptocapsa fallax, and the palynomorph Tucanopollis crisopolensis enabled us to date the interval as early Aptian. Based on the lithologies and microfossils recovered, we interpreted the studied interval as a continental setting that was episodically subjected to marine incursions. We propose three successive paleoenvironmental scenarios: (1) an initial lacustrine depositional setting with a non-marine biota; (2) a second stage, characterized by the presence of episodic marine influence in the sedimentary succession (as evidenced by radiolarians, foraminifera and ascidians), and (3) the return to continental settings dominated by aeolian dune fields. These environmental scenarios characterize the initial development of the Central Segment of the South Atlantic Ocean.